The modeling of 80 mm diameter cross flow turbine runner for mini/microhydro environmentally friendly power plant. (May 2019) - Purwanto; Budiyono; Hermawan
Abstract: Indonesian river's potentials on Mini or Microhydro fuelled power plants has not been maximally explored despite its big potentials of utilization. The 500 MW energy potentials of Mini or Microhydro throughout Indonesia have only reached the point of 4.5% while National Energy Management Blueprint in 2050 targeted 31% of renewable energy (RE) is coming from Micro hydro energy. The applications of 80 mm diameter cross flow turbine in a household scale have drawn an increase in its experience with 450 Watts of power produced through small discharge of 20 liters/second and 3-meter head. Cross flow turbines testing in 130 mm length and 80 mm diameter conducted using Mini / micro hydropower Plant in environmentally friendly power House drum. Lower investment and operational design cost also to be made on its aim to reach community group or individual segments.